2006
DOI: 10.1016/j.childyouth.2005.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Understanding maternal intentions to engage in home visiting programs

Abstract: Little is known as to why some parents choose to engage in voluntary home visitation services while others refuse or avoid services. To address this knowledge gap, this study tests several hypotheses about the factors that influence maternal intentions to engage in home visitation services and the link between these intentions and the receipt of a home visit. The sample consists of an ethnically diverse group of mothers identified as at-risk for parenting difficulties (N = 343). These mothers were offered home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 32 publications
2
31
0
4
Order By: Relevance
“…Children of women identified as having low psychological resources (i.e., limited intellectual functioning, mental health, and sense of personal control) were found to respond favorably to nurse-delivered home visits at six and 21 months of age (Olds et al, 2002). Greater parental engagement in services has been noted for parents who were considered at risk for parenting difficulties (Daro, McCurdy, Falconnier, & Stojanovic, 2003;McCurdy et al, 2006) than their counterparts. In the present study, CBC employed an individualized, responsive family centered approach to promote engagement similar to that used in other home visitation studies.…”
Section: Cbc and Family Riskmentioning
confidence: 89%
“…Children of women identified as having low psychological resources (i.e., limited intellectual functioning, mental health, and sense of personal control) were found to respond favorably to nurse-delivered home visits at six and 21 months of age (Olds et al, 2002). Greater parental engagement in services has been noted for parents who were considered at risk for parenting difficulties (Daro, McCurdy, Falconnier, & Stojanovic, 2003;McCurdy et al, 2006) than their counterparts. In the present study, CBC employed an individualized, responsive family centered approach to promote engagement similar to that used in other home visitation studies.…”
Section: Cbc and Family Riskmentioning
confidence: 89%
“…Regardless of the particular theory, studies of parent engagement have investigated only the intention construct. In general, findings show that parental intentions to enroll in a prevention program are strongly related to their participation (Dumas et al, 2007;McCurdy et al, 2006;Spoth et al, 1997).…”
Section: Theory Of Reasoned Action (Tra)=theory Of Planned Behavior (mentioning
confidence: 95%
“…Similarly, Dumas and colleagues (2007) found positive associations between children's elevated ratings for oppositional behavior and parent involvement in a parenting program. McCurdy et al (2006) found that parents of low-birth weight infants were more willing to receive home visiting services. Yet other research shows 60 K. A.…”
Section: Health Beliefs Model (Hbm) Constructsmentioning
confidence: 96%
See 1 more Smart Citation
“…Even in the case of a brief, three-session intervention delivered in the home for which families were given a financial incentive for participation, 17% of at-risk families chose not to enroll [43]. Families who decline interventions despite psychosocial risk factors may unfortunately be those in greatest need of assistance, such as first-time parents lacking knowledge regarding the challenges of child rearing or those uncomfortable with the model of in-home visitation (possibly due to unsuitable or unstable living conditions) [45]. Clearly, continued efforts to access and engage families at risk of nonparticipation and attrition are needed, with the understanding that barriers to participation are not static and will likely shift over time along with population trends in education, poverty and disparities.…”
Section: Moderators Of Outcomementioning
confidence: 99%